2014
DOI: 10.5742/meaa.2014.92483
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment among Egyptian Older Adults on Hemodialysis

Abstract: Background: Older patients are now the rule rather than the exception in hemodialysis (HD). Cognitive impairment is common among persons with end stage renal disease (ESRD) and is associated with poor outcomes. Aim: To assess the prevalence of cognitive impairment among older adults on HD and the association of different patients' demographics and characteristics with cognitive impairment. Materials and methods: A cross section study was conducted to assess the cognitive functions of elderly subjects on HD. 94… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Table 2 shows that the total average score (ACE-R) was lower than the cut-off points (78 points),15 , 16 confirming HD patients are at greater risk of developing dementia 5 , 7 - 13. Cognitive symptoms such as memory disorders, difficulty planning activities, impaired attention, decreased information processing speed, motor disability, and speech difficulty have been shown in mental health and CKD, revealing a negative influence of CKD on mental fitness 31…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 2 shows that the total average score (ACE-R) was lower than the cut-off points (78 points),15 , 16 confirming HD patients are at greater risk of developing dementia 5 , 7 - 13. Cognitive symptoms such as memory disorders, difficulty planning activities, impaired attention, decreased information processing speed, motor disability, and speech difficulty have been shown in mental health and CKD, revealing a negative influence of CKD on mental fitness 31…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is an increased odds ratio of 2.43 (95% CI, 1.38 to 4.29) for cognitive deficits in patients with an eGRF of <45 ml/min per 1.73 m2, even after adjusting for possible confounders 11 , 12. Another postulated theory for loss of cognitive functioning in CKD patients is that these patients often have underlying vascular disease such as diabetes mellitus and hypertension, which may contribute to cognitive impairment and, consequently, exert a negative influence on QOL 13…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…11 The prevalence of cognitive impairment in CKD patients ranges from 17% to 87% depending on severity. [12][13][14][15][16] Its prevalence among CKD patients is 20% in the United Kingdom, 17 75.5% in China, 18 and 53.8% in India. 19 A comparative cross-sectional study in Nigeria showed that the prevalence of cognitive impairment CKD patients is 35.3% whereas for the control group it is 6%.…”
Section: Introductionmentioning
confidence: 99%